DEVELOPMENT OF A LOADING TRAINING TOOL TO TRAIN WATER POLO JUMPS AND SHOTS BASED ON WATER BACK SPIDER (WBS) - Manzilina, Sarah; Sukur, Abdul; Hartono, Fajar Vidya (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
Penelitian ini bertujuan untuk mendapatkan data ilmiah tentang pengembangan alat latihan beban cabang olahraga polo air untuk meningkatkan hasil latihan lompatan dan tembakan pada atlet polo air. Sampel diambil berjumlah 20 atlet polo air yang telah berusia 16 tahun yang tergabung didalam pemusatan latihan daerah DKI Jakarta. Data dikumpulkan menggunakan kuisioner. Data kemudian dianalisis dengan menggunakan metode R&D dengan pendekatan kuantitatif. Berdasarkan uji hasil kelayakan oleh ahli terdapat nilai 98% pada efektifitas alat, 95% pada fungsi alat dan 75% pada desain alat. Berdasarkan uji reabilitas instrument menggunakan formula Kuder dan Richardson 21 (KR 21), sedangkan uji validitas untuk pilihan ganda menggunakan korelasi poin biserial. Pengujian reabilitas menggunakan SPSS terdapat nilai Cronch’s Alpha kuisioner uji efektifitas alat pembebanan berbasis water back spider (WBS) pada uji reabilitas adalah 1,48610103. Uji efektifitas diperoleh rerata pre-test 8,90 dan post-test 16,00 dengan standar deviasi 1,210 serta 1,747. Terdapat pada tabel uji-t dengan taraf signifikansi 0,05 memiliki Sig. (2-tailed) 0,001. Hasil p-value Sig. (2 – Sided) < 0,05, maka alat pembebanan berbasis water back spider (WBS) dapat meningkatkan hasil lompatan dan juga tembakan secara signifikan. This study aims to obtain scientific data on the development of water polo weight training tools to improve the results of jumping and shooting training for water polo athletes. Samples were taken totaling 20 water polo athletes who were 16 years old who were members of the DKI Jakarta regional training camp. Data was collected using a questionnaire. The data was then analyzed using the R&D method with a quantitative approach. Based on the feasibility test results by experts there is a value of 98% on the effectiveness of the tool, 95% on the function of the tool and 75% on the tool design. Based on the instrument reliability test using the Kuder and Richardson 21 (KR 21) formula, while the validity test for multiple choice uses biserial point correlation. Reliability testing using SPSS there is a Cronch's Alpha value for the effectiveness test questionnaire for the water back spider (WBS) based loading tool in the reliability test is 1.48610103. The effectiveness test obtained a mean pre-test of 8.90 and post-test of 16.00 with a standard deviation of 1.210 and 1.747. The t-test table with a significance level of 0.05 has Sig. (2-tailed) 0.001. The p-value result of Sig. (2 - Sided) <0.05, then the water back spider (WBS) based loading tool can significantly improve jumping and shooting results. Keywords: Water Polo, Jump, Shot.